AMS in basalts: Is there a need for prior demagnetization? - Schöbel, Stefan; de Wall, Helga; Rolf, Christian (Geophysical Journal International, 2013)
Keywords: Effusive volcanism.; Magnetic fabrics and anisotropy; Rock and mineral magnetism

AMS-NRM interferences in the Deccan basalts: Toward an improved understanding of magnetic fabrics in flood basalts - Schöbel, Stefan; de Wall, Helga (Journal of Geophysical Research. Solid Earth, 2014)
Keywords: AMS; AMS-NRM interference; Deccan LIP; flood basalts; flow direction; magnetic fabric

Continental rift-setting and evolution of neoproterozoic Sindreth basin in NW-India - Schöbel, Stefan; Sharma, Kamal K.; Hörbrand, Thorsten; Böhm, Theresa; Donhauser, Ines; de Wall, Helga (Journal of Earth System Science, 2017)
Keywords: Basin evolution; Continental setting; Malani Igneous Suite; NW India; Sindreth Basin

Deformation and granite intrusion in the Sirohi area, SW Rajasthan-Constraints on Cryogenian to Pan-African crustal dynamics of NW India - de Wall, Helga; Pandit, Manoj K.; Sharma, Kamal K.; Schöbel, Stefan; Just, Jana (Precambrian Research, 2014)
Keywords: Balda granite; Cryogenian; NW India; Rodinia; Sirohi region

Evolution and tectonic setting of the Malani – Nagarparkar Igneous Suite: A Neoproterozoic Silicic-dominated Large Igneous Province in NW India-SE Pakistan - de Wall, Helga; Pandit, Manoj K.; Donhauser, Ines; Schöbel, Stefan; Wang, Wei; Sharma, Kamal K. (Journal of Asian Earth Sciences, 2018)
Keywords: Crustal extension; Dyke swarm; Malani Igneous Suite; Geochemistry; Granite geochronology

In situ gamma radiation measurements in the Neoproterozoic rocks of Sirohi region, NW India - Scharfenberg, Lars; de Wall, Helga; Schöbel, Stefan; Minor, Alexander; Maurer, Marcel; Pandit, Manoj K.; Sharma, Kamal K. (Journal of Earth System Science, 2015)
Natural gamma ray measurements using a portable device were performed at 157 sites in the area around Sirohi town and Sindreth village in Rajasthan (NW India). This region comprises sedimentary rocks, metasediments, granites and gneisses that bear characteristic GR dose values and U/Th ratios corresponding with their specific geological history. A-type Malani granites and rhyolitic derivates, also referred as high heat production granites, show distinct differences as compared to the S-type Erinpura and Balda granites, most prominent in a high Th content of the former (up to 90 ppm). Sedimentary rocks in the Sirohi and Sindreth area are variable in their signatures reflecting their variable source rocks. In the area between the Balda and Paladi villages, northeast of Sirohi, measurements in vicinity of a N-S running shear zone, have shown U enrichment up to 8 ppm. This shear zone has been synkinematically mineralized with quartz and shows evidence of fluid infiltration into the host rocks in the vicinity of the shear zone. Erinpura granites have been altered due to fluid activity and show a light depletion of K (3.96%) and Th (20.11 ppm) as compared to the unaltered rocks (K, 4.06; Th 24.46 ppm). Enrichment of U (with a mean value of 13 ppm) has also been recorded in the lower clastic unit of the Sindreth Basin, especially within gritty conglomerates wherein migration and precipitation along fault planes is proposed.
Keywords: Gamma ray spectrometry; Neoproterozoic; uranium; Sirohi; Sindreth; NW India

Magnetostratigraphy and 40Ar-39Ar geochronology of the Malwa Plateau region (Northern Deccan Traps), central western India: Significance and correlation with the main Deccan Large Igneous Province sequences - Schöbel, Stefan; de Wall, Helga; Ganerod, Morgan; Pandit, Manoj K.; Rolf, Christian (Journal of Asian Earth Sciences, 2014)
Keywords: Ar-Ar geochronology; Deccan LIP; Deccan tectonomagmatic history; Eruption rate; Magnetostratigraphy; Malwa plateau

Variation of melting processes and magma sources of the early Deccan flood basalts, Malwa Plateau, India - Haase, Karsten; Regelous, Marcel; Schöbel, Stefan; Günther, Thomas; de Wall, Helga (Earth and Planetary Science Letters, 2019)
The Deccan flood basalts cover large parts of India and represent one of the largest volcanic provinces on Earth. We present geochemical and isotopic data on a magnetically defined stratigraphic section of lavas from the northern portion of the Deccan, the Malwa Plateau, which are dated at similar to 67.5 Ma. These are therefore some of the oldest Deccan lavas, erupted before the Main Deccan units further to the south. Although the younger Malwa Plateau lavas have undergone significant crustal contamination by at least two distinct crustal components, the older, more alkalic lavas are less contaminated and have similar isotope and trace element compositions to Reunion oceanic intraplate basalts. Our data therefore provide geochemical evidence for a contribution of the Reunion hotspot to the generation of the early Deccan flood basalts. Most lavas reflect fractional crystallization and assimilation of less than 10% of a crustal melt but samples with the highest SiO2 and Sr isotope compositions underwent more extreme crustal contamination. The composition of the least contaminated basalts from the Malwa Plateau suggests that the degree of partial melting increased significantly from the base to the top of the section. Most Malwa Plateau basaltic magmas formed by <5% partial melting of garnet peridotite in the Reunion mantle plume whereas the degree of melting in the Main Deccan Volcanic Province increased threefold and included MORB sources. Together, these geochemical variations indicate increasing degrees of melting between 68.5 and 65.4 Ma and a variation of the mantle sources from Reunion plume mantle to an increasing contribution from depleted upper mantle. These changes probably reflect lithospheric erosion by the mantle plume within 2 million years that allows melting of entrained upper mantle material. The geochemical data thus agree with geophysical models of significant thinning of cratonic lithosphere during the passage across mantle plumes. The magma evolution from alkaline to tholeiitic basalts observed in the Deccan flood basalts resembles that observed in early oceanic plume-related volcanism like Hawaii. (C) 2019 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2019-09-24